Polite Requests in Non-native Varieties of English: The Case of Ghanian English - Anderson, Jemima Asabea (Linguistica Atlantica, 2009)
Although several studies have been carried out on the theory of politeness, the definition of this notion varies among linguists and according to languages and cultures: what is polite and socially appropriate in one context or culture may be considered impolite or excessively polite in another. Further, rules of politeness may be transferred from a first language to a second language by learners who maintain hybridized usage due to these transfers. In this article we demonstrate the maintenance of some of these transfers in politeness strate. gies in Ghanaian English. This variety is influenced by the cultural norms of politeness of some Ghanaian languages whose speakers fuse native speaker conventions with English politeness conventions. We discuss herein some hybridized forms that result from cultural transfers from one Ghanaian language, Akan.